2022
DOI: 10.3389/fcimb.2022.837886
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacillus subtilis LF11 Protects Intestinal Epithelium Against Salmonella Infection

Abstract: Enteric diseases caused by Salmonella are prevalent in poultry farming. With the forbiddance of antibiotics in feedstuff industry, Bacillus subtilis (B. subtilis) preparation as antibiotic alternatives against Salmonella infection has gained increasing attention recently. However, the protection modes of B. subtilis against Salmonella infection in broilers are strain-specific. In this study, probiotic B. subtilis LF11 significantly reduced diarrhea and mortality of broilers caused by Salmonella braenderup (S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 67 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…The loss of mice weight is signi cantly inhibited in and 38328 groups compared to the SM group in the anti-Salmonella infection trial. It was reported that anti-Salmonella infection is caused by multiple mechanisms including coaggregation, signal interference, intestinal barrier and bacteriostatic activity [44]. In our results, all Bacillus displayed inhibitory effects against S. typhimurium CVCC541 in vitro, this suggests that the mechanism of the mice against Salmonella infections in vivo may be due to the bacteriostatic activity.…”
Section: Discussionsupporting
confidence: 63%
“…The loss of mice weight is signi cantly inhibited in and 38328 groups compared to the SM group in the anti-Salmonella infection trial. It was reported that anti-Salmonella infection is caused by multiple mechanisms including coaggregation, signal interference, intestinal barrier and bacteriostatic activity [44]. In our results, all Bacillus displayed inhibitory effects against S. typhimurium CVCC541 in vitro, this suggests that the mechanism of the mice against Salmonella infections in vivo may be due to the bacteriostatic activity.…”
Section: Discussionsupporting
confidence: 63%
“…Intestinal integrity is critical in maintain gut health 52 , especially when morphological changes negatively impact intestinal epithelial barrier during weaning 53 . Previous studies have observed an improved expression of intestinal tight junction genes and improved epithelial barrier function upon supplementation with bacillus-based probiotics 54 56 . Higher expression of the intestinal tight junction genes in our study agrees with the previous studies and may help explaining lower diarrhea scoring in the BS9 supplemented group.…”
Section: Discussionmentioning
confidence: 94%
“…The morphology of the small intestine directly mirrors the health of the gut, as well as its digestive and absorptive capabilities, which are critical for sustaining the intestinal immune system [ 68 , 69 , 70 ]. Longer villi correlate with epithelial cell proliferation and can stimulate cell mitosis, whereas shorter villi and deeper crypts are associated with nutrient malabsorption and diminished gastrointestinal function [ 71 , 72 , 73 , 74 ]. Our research has determined that dietary supplementation with B. subtilis RH results in an increase in the height of ileal villi and a decrease in crypt depth, thereby enhancing intestinal tissue structure in mice.…”
Section: Discussionmentioning
confidence: 99%